Analysis of Islamic Work Ethic on Job Satisfaction with Intrinsic Motivation Mediation Variables in Millennial Generation Employees - Iman, Iman Fauzi Sudirman; Firdaus, Achmad; Muhammad Ali, Zulkarnain (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2022)
This research aims to determine the impact of Islamic work ethic on job satisfaction with intrinsic motivation mediation variables in millennial generation employees. This type of research uses a quantitative description with explanatory research using a sample of 101 respondents. The data analysis method used in this research is descriptive analysis method, Structural Equation Modeling (SEM) with SmartPLS 3 software. The results show that Islamic work ethic has a significant and positive effect on job satisfaction both directly and indirectly. using the mediating variables of intrinsic motivation and job satisfaction. Keywords: Islamic Work Ethic, Intrinsic Motivation, Job Satisfaction